Microfacies and Sedimentary Environments of the Fahliyan Formation in the Folded Zagros Zone, SW Iran - Mahnaz Parvaneh Nejad Shirazi; Mohammad Bahrami; Fatemeh Dashtaby; Mohammad Sahraeyan (Institute of Advanced Engineering and Science, 2013)
The Fahliyan Formation (Lower Cretaceous) is composed of carbonate rocks and is composed of carbonate reservoir rocks in the Zagros Basin. The Zagros are located on the boundary between the Arabian and Eurasian lithosphere plates and are the orogenic response to a collision between Eurasia and advancing Arabia during the Cenozoic. The study area is located at the northwestern part of Kuh- E- Gadvan, 45 km northeast of Shiraz in the Folded Zagros Zone. Fahliyan Formation at Kuh- E- Gadvan, with a thickness of 325 meters consisted of thin to thick bedded limestone. The careful examination of thin sections led to the recognition of nine microfacies which was performed on the basis of skeletal and non- skeletal grains and matrix. Microscopic and macroscopic evidences show that Fahliyan Formation facies can be divided into four facies belts, on the basis of depositional features, specific of carbonate platforms of rimmed shelf type. These belts include tidal flat, lagoon, barrier and open marine environments. The Fahliyan Formation (Lower Cretaceous) is composed of carbonate rocks and is composed of carbonate reservoir rocks in the Zagros Basin. The Zagros are located on the boundary between the Arabian and Eurasian lithosphere plates and are the orogenic response to a collision between Eurasia and advancing Arabia during the Cenozoic. The study area is located at the northwestern part of Kuh- E- Gadvan, 45 km northeast of Shiraz in the Folded Zagros Zone. Fahliyan Formation at Kuh- E- Gadvan, with a thickness of 325 meters consisted of thin to thick bedded limestone. The careful examination of thin sections led to the recognition of nine microfacies which was performed on the basis of skeletal and non- skeletal grains and matrix. Microscopic and macroscopic evidences show that Fahliyan Formation facies can be divided into four facies belts, on the basis of depositional features, specific of carbonate platforms of rimmed shelf type. These belts include tidal flat, lagoon, barrier and open marine environments.